DAMPAK PAJAK EKSPOR CPO TERHADAP BEBERAPA ASPEK INDUSTRI CPO INDONESIA: SIMULASI MODEL EKONOMETRIK (IMPACTS OF CPO-EXPORT TAX ON SEVERAL ASPECTS OF INDONESIAN CPO INDUSTRY: SIMULATION OF ECONOMETRIC MODEL) - SUSILA, WAYAN R.; SETIAWAN, IDM. DARMA (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 1, No. 2 Juli 2001, 2012)
To control domestic supply and price of crude palm oil (CPO) and cooking oil, the government of Indonesia has imposed CPO-export tax since August 1994. As the CPO industry plays an important role in Indonesian economy, the imposition of the tax has perceived to have substantial impacts on various aspects of the industry, such as on investment, production, trade, farm income, and welfare distribution. In line of this issue, the main objective of this study is to assess these impacts using an econometric model of the industry. The results of the study reveal that this export tax policy has inhibited the growth rate of investment, production, export, and farm income. On the other hand, this policy has been an effective instrument to control domestic CPO and cocking oil price. Moreover, this policy has caused a substantial welfare transfer from producers to consumers and the government. To compromise these conflicting impacts, an alternative CPO tax formula is also proposed within this paper.
Keywords: Crude Palm Oil (CPO), Export Tax, Policy Impacts, Government of Indonesia